Ação antioxidante in vivo de extratos de erva mate (Ilex paraguariensis) livre e microencapsulados - Vargas, Bruna Krieger (2019)
Ilex paraguariensis is a plant widely distributed in the south of Brazil, with its widespread consumption through the mate. The yerba mate has several bioactive substances, such as saponins, methylxanthines and phenolic compounds, the latter better known for its antioxidant action. The inclusion of these components in the diet can contribute to the health of individuals. However, these biocomposites are sensitive and can be degraded by O2, light, pH and temperature. Thus, microencapsulation is being used with the aim of preserving these substances, ensuring that they are intact until reaching their target site in the body. We aimed to investigate the modulation of the antioxidant activity in vivo of extracts of microencapsulated yerba mate in comparison to free extracts. For this, aqueous extracts of yerba mate at different concentrations (5%, 10%, 15% and 20%) were characterized and tested in Saccharomyces cerevisiae yeasts. The extract selected was 15% with antioxidant activity of 4.39 ± 0.07 (mmol of Trolox/L), as well as maintaining the cellular survival (135.63 ± 11.39 CFU/mL) of the yeasts submitted to the stress model, radiation. The 15% erva-mate extract was lyophilized, presenting in its composition chlorogenic acid. Subsequently, this extract was microencapsulated by ionic gelling and the microcapsules were evaluated for particle size, solubility, encapsulation efficiency, morphological analysis and functional clusters, and subjected to an in vivo study in which 32 rats were divided into 4 groups: Control, Free Extract, Microencapsulated Extract and Empty Microcapsule. In the 30 day period the animals received via gavage their respective treatments and in the end we evaluated the enzymes superoxide dismutase, catalase and glutathione peroxidase, antioxidant activity and lipid peroxidation. Microencapsulation was able to generate particles with a mean diameter of 91.42 μm, mean solubility of 21.2% and encapsulation efficiency of 64.73%. Although scanning electron microscopy showed an irregular shape of the microcapsules, spectroscopy showed that ionic gelation was able to microencapsulate and protect the bioactive compounds of the yerba mate. In the in vivo protocol with Wistar rats the microcapsules containing yerba-mate showed a greater antioxidant capacity in the plasma and reduction of the lipid peroxidation in the cerebral tissue. Regarding the behavior of the antioxidant enzymes, the microencapsulated extract and the free extract attenuated the levels of superoxide dismutase, with significant difference only to the empty microcapsule group. While the free extract alone was able to reduce the enzymatic levels of catalase and glutathione peroxidase in the liver. The results of our study in rodents suggest that ingestion of yerba mate in its microencapsulated form is the most efficient way to promote antioxidant defenses in the body and reduce lipid peroxidation. We conclude that yerba mate may be an important element in the diet of animals, since regular consumption during 30 days characterized health benefits. However, further studies are needed to understand how each bioactive substance is absorbed.